Adolescents Engaged in Radicalisation and Terrorism: A Dimensional and Categorical Assessment - Bronsard, Guillaume; Cohen, David; Diallo, Issaga; Pellerin, Hugues; Varnoux, Aurélien; Podlipski, Marc-Antoine; Gerardin, Priscille; Boyer, Laurent; Campelo, Nicolas (Frontiers in Psychiatry, 2022)
Since 2010 and the founding of the Islamic State, the radicalisation phenomenon in Europe has involved more adolescents and converts to Islam than in previous Islamist terrorist group movements (e.g., Al-Qaeda). In most cases, these adolescents are ‘homegrown terrorists’, a challenging difference, as they are in confrontation with their home and societal environment. As a new and emerging phenomenon, radicalisation leads to many questions. Are empathic capacities altered? Are they presenting psychiatric pathologies or suicidal tendencies that explain why they put themselves in serious dangers? Are they just young delinquents who simply met a radical ideology? In January 2018, by special Justice Department authorization, we contacted all minors (N = 31) convicted in France for ‘criminal association to commit terrorism’. We assessed several sociodemographic, clinical and psychological variables, including empathy and suicidality, in half of them (N = 15) and compared them with 101 teenagers convicted for nonterrorist delinquency who were placed in Closed Educational Centres (CEC). The results show that adolescents engaged in radicalisation and terrorism do not have a significant prevalence of psychiatric disorders, suicidal tendencies or lack of empathy. It also appears that they have different psychological profiles than delinquent adolescents. ‘Radicalised’ adolescents show better intellectual skills, insight capacities and coping strategies. In addition, the manifestation of their difficulties is less externalized than adolescents from the CEC, having committed very few delinquent acts.